Crystal structure of (18-crown-6)potassium(I) [(1, 2, 3, 4, 5-η)-cycloheptadienyl][(1, 2, 3-η)-cycloheptatrienyl]cobalt(I). (March 2015) - Brennessela, William W.; Ellis, John E.
No abstract available